Toxicology and Health Benefits of Plant Alkaloids - Chikowe, Ibrahim; Mtewa, Andrew G.; Sesaazi, Duncan C. (Poisonous Plants and Phytochemicals in Drug Discovery, 2020)
Alkaloids are a class of natural products containing carbon (C), hydrogen (H), nitrogen (N), and usually oxygen (O). These compounds have been categorized into different classes based on their sources, pharmacokinetics, and chemical structure. They include isoquinoline alkaloids, indole alkaloids, pyrroloindole alkaloids, piperidine alkaloids, aporphine alkaloids, pyridine alkaloids, methylxanthine derivatives, vinca alkaloids, lycopodium alkaloids, indole beta-carboline, and erythrine by-products [1, 2]. Alkaloids are derived from plants (especially in
Keywords: Alkaloids; Natural products; Toxicology; Health Benefits